Hydrophytic Cyperaceae from the Araguaia river basin, Brazil - Adriana Luiza Ribeiro de Oliveira; André dos Santos Bragança Gil; Claudia Petean Bove (Rodriguésia)
Abstract Cyperaceae is a cosmopolitan family with over 5,000 species, which are often found in wet habitats. In this study we found 31 hydrophylic species of Cyperaceae, belonging to 10 genera (Ascolepis, Calyptrocarya, Cyperus, Eleocharis, Fimbristylis, Fuirena, Lipocarpha, Pycreus, Rhynchospora and Scleria), that occur in the Araguaia River Basin, located mainly within the Brazilian Cerrado (savanna). Short descriptions, geographic distribution, illustrations, identification keys and comments are presented.